Absorbable monofilament suture and preparation method thereof

By using wet spinning of high-deacetylated, high-molecular-weight chitosan and polycarboxylic acid ion crosslinking technology, the problem of insufficient mechanical properties of chitosan sutures has been solved, and absorbable sutures with excellent mechanical properties, biocompatibility and controllable degradation have been prepared, meeting medical standards.

CN121102548APending Publication Date: 2025-12-12吴奕光
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202511365601.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-23
Publication Date
2025-12-12

AI Technical Summary

Technical Problem

Existing absorbable sutures such as catgut and collagen sutures have problems such as poor flexibility, easy infection, large tissue reaction or rapid degradation, and short strength retention time. Pure chitosan materials have insufficient mechanical properties and cannot meet the requirements of surgical suturing.

Method used

Using chitosan with high deacetylation degree and high molecular weight as raw material, nascent fibers are prepared by wet spinning, and then ion-crosslinked with polycarboxylic acid solution under specific conditions to construct a stable ion-crosslinked network and enhance mechanical properties.

Benefits of technology

It significantly improves the mechanical properties of absorbable sutures, meeting medical standards, while maintaining good biocompatibility and controllable degradation, thus ensuring biocompatibility without the use of toxic chemical cross-linking agents.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121102548A_ABST
    Figure CN121102548A_ABST
Patent Text Reader

Abstract

The invention discloses an absorbable monofilament suture and a preparation method thereof, and the preparation method comprises the following steps: S1, dissolving chitosan in a dilute acid solution to form a spinning solution; s2, sequentially carrying out filtering treatment and vacuum defoaming treatment on the spinning solution; s3, the spinning solution treated in the step S2 is extruded into a coagulating bath through a spinning component, and nascent fibers are formed; s4, carrying out water washing treatment on the nascent fiber; s5, immersing the nascent fiber treated in the step S4 into a polycarboxylic acid solution to carry out an ionic cross-linking reaction; s6, the fibers subjected to the ionic cross-linking reaction in the step S5 are sequentially subjected to water washing treatment and drying treatment, the absorbable monofilament suture is obtained, the mechanical properties such as dry-state holding stress and the like of the finally obtained monofilament suture are synergistically and remarkably improved, use of a toxic chemical cross-linking agent is avoided, and the production cost is reduced. And the suture is ensured to finally have good biocompatibility and controllable degradation performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of biomedical materials technology, specifically to an absorbable monofilament suture and its preparation method. Background Technology

[0002] Medical surgical sutures are sterile sutures used for wound healing, hemostasis, tissue ligation, and tissue fixation. Absorbable surgical sutures, after being implanted in the human body, can be degraded and absorbed or metabolized and excreted, avoiding the secondary pain caused by suture removal, and their clinical application is becoming increasingly widespread.

[0003] Currently, absorbable sutures mainly include natural materials such as catgut and collagen sutures, as well as synthetic materials. Catgut sutures have disadvantages such as poor flexibility, susceptibility to infection, and significant tissue reaction; collagen sutures, on the other hand, degrade quickly, have a short duration of strength retention, and lack antibacterial properties.

[0004] Chitosan (CS), a product of chitin after deacetylation, possesses excellent biocompatibility, biodegradability, antibacterial properties, and wound-healing properties, making it an ideal material for preparing absorbable sutures. However, pure CS materials have poor mechanical properties, making it difficult to meet the strength requirements of surgical sutures. Existing technologies, such as patent US4018678 and literature (Ogura et al, Polymer Bulletin, 1980), disclose methods for preparing CS fibers using wet spinning, but the mechanical properties of the resulting fibers still need improvement.

[0005] To improve the performance of CS materials, various techniques have been explored. Polycarboxylic acids, such as citric acid (CA), have been used for crosslinking modification of biomaterials due to their good biocompatibility and safety. The crosslinking mechanism involves the protonated amino group (-NH3) in the CS molecule. + The ionized carboxyl group -COO- in the CA molecule forms an ionic crosslinking network, thereby enhancing the mechanical properties of the material. However, how to apply polycarboxylic acid ionic crosslinking technology to the preparation of CS monofilament sutures to obtain absorbable sutures with excellent mechanical properties, suitable degradation rate, and good biocompatibility remains a technical problem to be solved in this field. Summary of the Invention

[0006] The technical problem to be solved by the present invention is to overcome the shortcomings of insufficient mechanical properties of CS monofilament sutures in the prior art, and to provide an absorbable monofilament suture and its preparation method. Through a specific polycarboxylic acid ion crosslinking process, the mechanical properties of CS monofilament sutures are significantly improved, while maintaining good biocompatibility and degradability.

[0007] To solve the above-mentioned technical problems, the present invention adopts the following technical solution:

[0008] A method for preparing absorbable monofilament suture includes the following steps: S1: dissolving CS raw material in a dilute acid solution to form a spinning solution; S2: sequentially filtering and vacuum degassing the spinning solution; S3: extruding the spinning solution treated in step S2 through a spinneret into a coagulation bath to form nascent fibers; S4: washing the nascent fibers; S5: immersing the nascent fibers treated in step S4 into a polycarboxylic acid solution for ionic crosslinking reaction; S6: sequentially washing and drying the fibers after the ionic crosslinking reaction in step S5 to obtain absorbable monofilament suture.

[0009] In some embodiments, the following technical features are also included:

[0010] The CS raw material has a degree of deacetylation greater than 84.5% and a molecular weight greater than 7.0 × 10⁻⁶. 6 The volume percentage concentration of the dilute acid solution is 1.0% to 3.0%, and the dilute acid solution can be a dilute acetic acid solution; the mass-volume percentage concentration of the solids in the spinning solution is 1% to 4%.

[0011] In some embodiments,

[0012] In step S2, the filtration process uses a 250-400 mesh filter cloth for vacuum filtration; the vacuum degassing process takes 1-5 hours.

[0013] In some embodiments,

[0014] In step S3, the coagulation bath contains ethanol with a mass percentage concentration of 1.0 to 4.5% and sodium hydroxide with a mass percentage concentration of 2.0 to 6.0%.

[0015] In some embodiments,

[0016] In step S3, after the spinning solution is extruded from the spinneret, a constant exhaust pressure of 0.5 to 0.9 MPa is applied to the spinneret.

[0017] In some embodiments,

[0018] In steps S4 and S6, the water washing process includes soaking in sufficient deionized water for 12 to 36 hours, changing the water 1 to 3 times during this period.

[0019] In some embodiments,

[0020] The drying process in step S6 includes hanging the product to air dry for 26 to 36 hours at a temperature of 15 to 25°C and a relative humidity of 45 to 75%.

[0021] In some embodiments,

[0022] In step S5, the mass percentage concentration of the polycarboxylic acid solution is 10-30%, and the polycarboxylic acid is one of CA, tartaric acid, malic acid, or succinic acid.

[0023] In some embodiments,

[0024] In step S5, the pH of the polycarboxylic acid solution is adjusted to 5.5–6.5 using sodium hydroxide solution, the reaction temperature is 20–90°C, and the reaction time is 1–3 hours.

[0025] The present invention also adopts the following technical solution:

[0026] An absorbable monofilament suture, the absorbable monofilament suture being prepared using the method described above.

[0027] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0028] This invention utilizes high-molecular-weight, high-deacetylation-degree CS to ensure excellent spinnability and fiber formation properties in the spinning solution. Optimized wet spinning process parameters, including specific coagulation bath composition and exhaust pressure control, yield dense nascent fibers. Furthermore, by placing the nascent fibers in a polycarboxylic acid solution within a specific pH, concentration, and temperature range for ionic crosslinking, a stable ionic crosslinking network is constructed between the CS molecular chains. This crosslinking network effectively enhances the intermolecular forces. The high-molecular-weight, high-deacetylation-degree CS provides more amino groups and molecular chain strength; the optimized wet spinning process forms a dense nascent fiber structure; and the specific ionic crosslinking process constructs an intermolecular crosslinking network. These three factors work synergistically to significantly improve mechanical properties, including the dry-state knot holding stress of the final monofilament suture, enabling it to meet the requirements of the YY 1116-2020 standard. Simultaneously, the mild conditions of this ionic crosslinking process avoid the use of toxic chemical crosslinking agents, ensuring the suture exhibits good biocompatibility and controllable degradation performance.

[0029] In some embodiments, it also has the following beneficial effects:

[0030] By using a polycarboxylic acid solution with a mass percentage concentration of 10-30%, sufficient cross-linking points can be provided to ensure cross-linking density, thereby obtaining a better mechanical reinforcement effect.

[0031] By adjusting the pH of the polycarboxylic acid solution to 5.5–6.5 using sodium hydroxide solution, a pH balance was created that ensures effective ionization of the carboxyl group (-COO-) to react with -NH3. + The optimal reaction environment, which combines the properties of CS with those of CS, prevents CS from dissolving in an overly acidic environment and helps to form a uniform and stable cross-linked structure.

[0032] By controlling the reaction temperature to 20–90℃ and the reaction time to 1–3 hours, the rate and extent of the crosslinking reaction can be regulated, avoiding insufficient reaction leading to insignificant improvement in mechanical properties, or excessive reaction leading to fiber embrittlement, thereby maintaining good material toughness while obtaining high mechanical properties. Attached Figure Description

[0033] Figure 1 This is a flowchart of a method for preparing an absorbable monofilament suture according to an embodiment of the present invention.

[0034] Figure 2a and Figure 2b This is a trend diagram showing the influence of different CA solution concentrations on the mechanical properties of composite monofilaments.

[0035] Figure 3a and Figure 3b This is a trend diagram showing the influence of different reaction temperatures on the mechanical properties of composite monofilaments.

[0036] Figure 4a and Figure 4b This is a trend diagram showing the influence of different reaction times on the mechanical properties of composite monofilaments.

[0037] Figure 5a and Figure 5b This is a trend diagram showing the influence of pH on the mechanical properties of composite monofilaments prepared under different reaction systems.

[0038] Figure 6a and Figure 6b This is a macroscopic morphology diagram of a composite monofilament.

[0039] Figure 7 This is a comparison chart of the color development of the heavy metal content test reaction.

[0040] Figure 8 This is a graph showing the change in the residual rate of monofilament suture after in vitro enzymatic degradation over time.

[0041] Figure 9 This is a graph showing the change in residual stress value over time after in vitro enzymatic degradation of composite monofilament sutures.

[0042] Figures 10a to 10e These are scanning electron microscope images of composite monofilament sutures after different cycles of in vitro enzymatic degradation.

[0043] Figures 11a to 11f This is a graph showing the morphological changes of human epidermal cells (Hacat) in different treatment groups over three days after drug administration.

[0044] Figure 12 This is a graph showing the change in Hacat's survival rate over time.

[0045] Figures 13a to 13fThis is a graph showing the morphological changes of mouse fibroblasts (L929) in different treatment groups within three days after drug administration.

[0046] Figure 14 This is a graph showing the survival rate of L929 over time. Detailed Implementation

[0047] The present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments. The following embodiments are only used to more clearly illustrate the technical solutions of the present invention, and are therefore only examples, and should not be used to limit the scope of protection of the present invention.

[0048] The core of this invention lies in providing a method for preparing polycarboxylic acid ion-crosslinked CS absorbable monofilament sutures. By precisely controlling raw material parameters, spinning process, and crosslinking reaction conditions, a stable ion-crosslinked network is constructed between molecular chains, aiming to significantly improve the mechanical properties of CS monofilament sutures to meet medical standards while maintaining their inherent biocompatibility and biodegradability. This method uses high-deacetylation, high-molecular-weight CS as raw material, which is wet-spun into nascent fibers, and then ion-crosslinked using a polycarboxylic acid solution. This utilizes the protonated amino group (-NH3) in the CS molecule... + With the ionized polycarboxylic acid -COO in the polycarboxylic acid molecule - The ionic bonding between them forms an intermolecular cross-linking network inside the fiber, thereby greatly enhancing its mechanical strength and solving the problem of insufficient mechanical properties of pure CS monofilament sutures. This allows for the preparation of absorbable sutures that combine excellent mechanical properties, biocompatibility, and controllable degradation.

[0049] This invention provides a method for preparing absorbable monofilament sutures. CS monofilaments are prepared using a wet spinning method, and then ion-crosslinked by immersion in a polycarboxylic acid solution to prepare absorbable surgical sutures. The degree of deacetylation (DD) is >84.50%, and the molecular weight (MW) is >7.0 × 10⁻⁶. 6 Using CS as raw material, a spinning solution was prepared with a solids concentration of 1.0–4.0 g / 100 mL, filtered, and degassed under vacuum. The coagulation bath consisted of a mixed solution of 1.0%–4.5% (w / w) ethanol and 2.0%–6.0% (w / w) sodium hydroxide, and spinning was performed using a wet spinning machine. The nascent fibers were soaked and washed with water, then immersed in a polycarboxylic acid solution of a specific concentration, pH value, and temperature for ionic cross-linking for a period of time, followed by soaking and washing with water, and then hung to dry. The prepared monofilament sutures met the requirements of the "Pharmaceutical Industry Standard of the People's Republic of China" YY 1116-2020 for the tensile strength of absorbable surgical sutures (single strand) and other relevant requirements, demonstrating promising clinical application prospects.

[0050] CS (cartilage styrene) inherently possesses advantages such as biocompatibility, antibacterial properties, hemostasis, scar inhibition, and biodegradability, making it an ideal material for absorbable surgical sutures. However, its poor mechanical properties prevent it from achieving the desired effects. This invention proposes to prepare CS monofilaments by wet spinning high molecular weight squid cartilage CS, followed by ion crosslinking in a polycarboxylic acid solution, to prepare a polycarboxylic acid ion-crosslinked CS absorbable surgical suture with good mechanical properties, biocompatibility, and biodegradability.

[0051] Add appropriate amounts of deionized water and glacial acetic acid to a 500mL beaker, stir with an electric mixer, and slowly add a certain mass of CS powder (DD>84.5%, MW>7.0×10). 6 Heat to 40–70°C and maintain for 1–3 hours, then stir overnight at room temperature to ensure complete dissolution of CS. The spinning solution is designed with a solids content of 1.0%–4.0% (w / v), an acetic acid concentration of 1.0–3.0% (v / v), and a spinning solution volume of 300 mL. This is because as long as DD > 65%, even with high molecular weight CS (MW > 7.0 × 10⁻⁶), [the desired effect can be achieved]. 6 Both CS and CS are soluble in dilute acetic acid, so a concentration of 1-3% is reasonable. Using a 1.0-3.0% dilute acetic acid solution can ensure that CS molecules are fully dissolved to form a uniform and stable spinning solution without excessive degradation of the CS molecular chains.

[0052] Compared to low-viscosity spinning solutions, high-viscosity spinning solutions have greater cohesive energy in CS (cohesive core), which is more conducive to forming stable spinning streams.

[0053] To prevent spinneret blockage or uneven filtrate diameter in some nascent fibers due to large, invisible insoluble particles during spinning, the spinning solution is filtered through a Buchner funnel made of 250-400 mesh nylon mesh. The filtrate is then stirred overnight. The filtrate is transferred to the solution tank of the spinning machine, and a vacuum pump is connected. The solution tank is then evacuated for 1-5 hours to completely remove small air bubbles generated when the spinning solution is poured into the tank.

[0054] The coagulation bath is a mixed solution of 1.0%–4.5% (w / w) ethanol and 2.0%–6.0% (w / w) sodium hydroxide, with a volume of approximately 9 L. Wet spinning is used. It is crucial to wait until the spinning solution flows out of the swan-neck spinneret before turning on the air compressor; otherwise, it will cause an increase in air bubbles within the nascent fibers. The presence of air bubbles effectively reduces the diameter of the monofilament at the bubble-covered areas, naturally leading to breakage at those areas and thus reducing the tensile strength at break. The exhaust pressure of the air compressor is kept constant at 0.5–0.9 MPa.

[0055] The nascent fibers are soaked in sufficient deionized water for 12–36 hours, with the water changed 1–3 times during this period. Afterward, they are hung to dry in an environment of 15–25℃ and RH (relative humidity) of 55–75% for 26–36 hours, until there are no obvious water droplets on the fiber surface.

[0056] Prepare a 10%–30% (w / w) aqueous solution of a polycarboxylic acid, and adjust its pH to 5.5–6.5 with a 10% (w / w) NaOH solution. Immerse the CS monofilaments in the polycarboxylic acid solution at 20–90°C for 1–3 hours. After the reaction, soak the monofilaments in sufficient deionized water for 12–36 hours, changing the water 1–3 times. Then hang them to dry in an environment of 15–25°C and RH = 45–75% for 26–36 hours. Preferably, soaking in a 70°C polycarboxylic acid solution helps accelerate the penetration of CA small molecules into the CS gel fibers and their participation in ionic cross-linking. Since CS gel only degrades at high temperatures in concentrated alkali, the degradation of CS gel in the polycarboxylic acid solution in this embodiment is negligible.

[0057] Example 1

[0058] This embodiment provides a method for preparing absorbable monofilament sutures, such as... Figure 1 As shown, it includes the following steps:

[0059] S1: Prepare the spinning solution. Weigh 7.5 g of a spinning solution with a degree of deacetylation (DD) of 85.0% and a molecular weight (MW) of 9.0 × 10⁻⁶. 6 CS powder was added. 294.0 mL of deionized water was measured into a 500 mL beaker, and 6.0 mL of glacial acetic acid (i.e., acetic acid volume percentage concentration of 2.0%) was added. The CS powder was slowly added under electric stirring. The mixture was heated to 55°C and stirred for 2 hours, then stirred overnight at room temperature to ensure complete dissolution of the CS, yielding a spinning solution with a solids mass volume percentage concentration of 2.5%.

[0060] S2: Post-treatment of spinning solution. The spinning solution was filtered using a Buchner funnel lined with 300-mesh nylon filter cloth to remove insoluble particles that might clog the spinneret orifices. The filtrate was transferred to the solution tank of the spinning machine, and a vacuum pump was connected. Vacuum degassing was performed for 3 hours using the exhaust and intake valves to remove air bubbles from the spinning solution.

[0061] S3: Wet spinning. The coagulation bath is an aqueous solution containing 2.0% ethanol and 5.0% sodium hydroxide by mass, with a total volume of approximately 9L. The spinning machine is started, and after the spinning solution flows steadily out of the gooseneck spinneret, the air compressor is turned on to apply a constant exhaust pressure of 0.7MPa to the spinneret, causing the fine stream of spinning solution to enter the coagulation bath and solidify, forming nascent fibers.

[0062] S4: Post-treatment of nascent fibers. Immerse the collected nascent fibers in sufficient deionized water for 24 hours, changing the deionized water twice during this period to remove residual acid and alkali.

[0063] S5: Ionic crosslinking. Prepare a 15% (w / w) aqueous solution of CA. Adjust the pH of the CA solution to 6.0 using a 10% (w / w) sodium hydroxide solution. Immerse the pure CS monofilament treated in step S4 into the CA solution preheated to 70°C and react for 2.5 hours.

[0064] S6: Post-crosslinking treatment. After the reaction is complete, the monofilament is removed and immersed in sufficient deionized water for 24 hours, during which the deionized water is changed twice to remove unreacted CA. Afterward, the monofilament is dried in an environment of 20°C and 45% relative humidity, and hung to dry for 26 hours to obtain the finished absorbable monofilament sewing thread.

[0065] Performance Verification: The absorbable monofilament suture prepared in this embodiment exhibits significantly higher dry-state knot holding stress than pure CS monofilament without ion crosslinking treatment. Its mechanical properties, heavy metal content, in vitro enzymatic degradation performance, and cytotoxicity were verified according to the following framework: Mechanical Property Testing: The knot holding stress and tensile strength at break of the monofilament suture were tested according to the YY 1116-2020 standard. The experimental verification results are as follows:

[0066] The holding stress is 87.97±3.63MPa; the non-holding stress is 88.07±5.27MPa.

[0067] The tensile strength at break was 5.79 ± 0.91%.

[0068] Heavy metal content test: The test was conducted in accordance with GB / T 14233.1-2008, and the results showed that the heavy metal content was lower than the standard limit.

[0069] In vitro enzymatic degradation performance: Sutures were immersed in lysozyme solution and kept at a constant temperature of 37°C with shaking. Samples were taken periodically to test their residual mass and residual stress (BSR). Residual mass at week 5: 86.84±0.91%; BSR at week 5: 84.08±6.59%.

[0070] Cytotoxicity test: The MTT assay was used to test the toxicity of the extract to L929 cells and HaCaT cells. The cell viability should be greater than 70% (standard requirement), preferably greater than 100% (indicating growth promotion potential).

[0071] L929 cell viability (1d / 2d / 3d): 109.64% ± 10.28% on day 1, 108.01% ± 14.33% on day 2, and 113.14% ± 14.33% on day 3.

[0072] HaCaT cell survival rates (1d / 2d / 3d): 107.95% ± 8.70% on day 1, 109.27% ​​± 2.30% on day 2, and 104.18% ± 11.10% on day 3.

[0073] Example 2

[0074] This embodiment mainly demonstrates the changes in CS raw material parameters, dilute acid concentration, spinning solution concentration, and polycarboxylic acid concentration. This embodiment provides a method for preparing absorbable monofilament thread, the steps of which are basically the same as in Example 1, except that the degree of deacetylation of the CS raw material is 90.0%, and the molecular weight is 8.0 × 10⁻⁶. 5 The dilute acid used is acetic acid, with a volume percentage concentration of 3%; the solids in the spinning solution have a mass percentage concentration of 3.5%. In step S5, the polycarboxylic acid used is CA, with a mass percentage concentration of 25%, and the crosslinking reaction temperature is 50°C. Other step parameters, such as vacuum degassing time, coagulation bath composition, exhaust pressure, washing and drying conditions, and the pH and time of the crosslinking reaction, are the same as in Example 1. This example aims to verify that even after changing the raw material specifications and key solution concentrations, a qualified absorbable monofilament thread can still be prepared. Experimental results show that the holding stress is 77.80±3.84 MPa, and the tensile strength at break is 5.67±1.23%.

[0075] Example 3

[0076] This embodiment mainly demonstrates the changes in other parameters in the process flow. This embodiment provides a method for preparing absorbable monofilament thread, the steps of which are basically the same as those in Embodiment 1, except that: in step S2, the vacuum degassing treatment time is 1 hour. In step S3, the coagulation bath contains 3.5% ethanol and 3.0% sodium hydroxide by mass percentage. In step S3, the constant exhaust pressure applied to the spinneret is 0.55 MPa. In steps S4 and S6, the water washing treatment includes: soaking in sufficient deionized water for 36 hours, changing the water once during this period. The drying treatment in step S6 includes: hanging to dry at 18°C ​​and 55% relative humidity for 36 hours. In step S5, the polycarboxylic acid is CA, the pH of the CA solution is adjusted to 5.8 using sodium hydroxide solution, and the reaction temperature is 90°C. The remaining step parameters, such as CS raw material specifications, acetic acid concentration, spinning solution concentration, and CA concentration, are the same as in Embodiment 1. Experimental results showed that the holding stress was 79.73 ± 7.02 MPa, and the tensile strength at break was 5.93 ± 1.63%.

[0077] Experimental Example

[0078] The following is a detailed description of the entire process of a specific experimental example.

[0079] To prevent spinneret blockage or uneven filtrate diameter in some nascent fibers due to large, invisible insoluble particles during spinning, the spinning solution was filtered through a Buchner funnel made of 300-mesh nylon mesh filter cloth. The filtrate was stirred overnight. It was then poured into a solution tank, and a vacuum pump was used to evacuate and degas the solution for 3 hours to completely remove any small air bubbles generated when the spinning solution was poured into the solution tank.

[0080] The coagulation bath is a mixed solution of 2.0% (w / w) ethanol and 5.0% (w / w) sodium hydroxide, with a volume of about 9L. Wet spinning is used. Note that the air compressor should only be turned on after the spinning solution flows out of the gooseneck spinneret, otherwise it will cause an increase in air bubbles in the nascent fiber. The exhaust pressure of the air compressor is kept constant at 0.7MPa.

[0081] The nascent fibers were soaked in sufficient deionized water for 24 hours, with the water changed twice during this period. They were then hung to dry for 24 hours at 20℃ and RH=65%. During this crosslinking process, the obtained CS / CA composite monofilaments were affected by factors such as the concentration of the CA solution, reaction temperature, reaction time, and pH value of the reaction system. Specific experimental results are shown below.

[0082] The trend of the effect of CA solution concentration on the holding mechanical properties of CS / CA composite monofilaments is as follows: Figure 2a and Figure 2b As shown. Figure 2a This is a trend graph; the horizontal axis represents the concentration of CA solution, the black vertical axis on the left represents tensile strength, and the red vertical axis on the right represents elongation at break. Figure 2b The graph shows the elongation at break on the horizontal axis and the tension on the vertical axis. Mechanical properties were tested at a reaction temperature of 50℃, pH=6, a reaction time of 2.5h, and an ambient RH of 45%. With increasing CA solution concentration (w / w), the stress holding the CS / CA composite monofilament continuously increased within the range of 10%–15%, reaching a peak at 15% (w / w), exhibiting the maximum elastic limit.

[0083] The following graph shows the trend of stress and tensile strength of the bonded CS / CA composite monofilament obtained by changing the temperature of the ionic crosslinking reaction under the following conditions: CA solution concentration of 15% (w / w), pH = 6, reaction time of 2.5 h, and ambient RH = 45%. Figure 3a and Figure 3b As shown. Figure 3aThis is a trend chart. The horizontal axis represents temperature, the black vertical axis on the left represents temperature, and the red vertical axis on the right represents elongation at break. Figure 3b This is a stretching curve, with the horizontal axis representing elongation at break and the vertical axis representing tension. Increasing the reaction temperature can accelerate CA permeation within the same timeframe, allowing it to participate in the ionic cross-linking reaction, i.e., increasing the amount of -COO- on the ionized CA and -NH3 on the CS monofilament. + Ionic crosslinking forms more ionic bonds, resulting in stronger inter-segmental forces in the monofilament molecules and improving their physical and mechanical properties. The conclusion is that the CS / CA composite monofilament reaches its highest stress at 70℃, making 70℃ the optimal reaction temperature.

[0084] The trend of the effect of reaction time on the knot-holding mechanical properties of CS / CA composite monofilaments is as follows: Figure 4a and Figure 4b As shown, Figure 4a This is a trend chart. The horizontal axis represents time, the black vertical axis on the left represents Tension, and the red vertical axis on the right represents Elongation at break. Figure 4b This is a stretching curve, with the horizontal axis representing elongation at break and the vertical axis representing tension. The graph shows that this is due to the interaction of -COO- and -NH3-. + The ionic cross-linking of CS and CA enhances the interaction forces between molecular chain segments. Compared with pure CS monofilament, the ionic cross-linking of CS and CA can significantly increase the stress of the monofilament and reduce the tensile strength at break. This makes the monofilament suture less prone to large tensile deformation, ensuring better wound suturing during the wound healing process.

[0085] In a CA solution with a concentration of 15% (w / w), a reaction temperature of 70℃, pH = 6, and an ambient RH of 45%, the stress in the CS / CA composite monofilament continuously increased as the reaction time gradually increased from 0 h to 2.5 h. However, when the reaction time exceeded 2.5 h, further increasing the time for ionic cross-linking resulted in an excessive number of ionic bonds within and between the molecular chains. Under external forces, the molecular chains were difficult to smooth, exhibiting hardness and brittleness with insufficient toughness. Consequently, the transverse shear force weakened, and the stress showed a decreasing trend. Therefore, the optimal reaction time is 2.5 h.

[0086] The influence of pH on the mechanical properties of composite monofilaments prepared under different reaction systems is as follows: Figure 5a and Figure 5b As shown. Figure 5a This is a numerical statistical graph. The horizontal axis represents pH, the black vertical axis on the left represents Tension, and the red vertical axis on the right represents Elongation at break. Figure 5b The graph shows the elongation at break on the x-axis and the tension on the y-axis. With a CA solution concentration of 15% (w / w), a reaction temperature of 70℃, a reaction time of 2.5 h, and an ambient RH of 45%, changing the pH of the reaction system affects the degree of ionic cross-linking between CA and CS. At pH 4, the CS monofilament partially dissolves in the CA solution, and the CS monofilament cannot maintain its linear shape. The composite monofilament prepared at pH 5 is stiffer, locally rough, and breaks when knotted. Figure 5a and 5b It can be concluded that the CS / CA composite monofilament suture obtained when the pH of the reaction system is 6 under these conditions can achieve the maximum stress and a relatively ideal tensile strength at break.

[0087] Experiments were conducted under the aforementioned optimal reaction conditions. A 15% (w / w) CA aqueous solution was prepared, and its pH was adjusted to 6.0 with a 10% (w / w) NaOH solution. The CS monofilament was then immersed in the CA solution at 70°C for 2.5 h. After the reaction, the monofilament was immersed in sufficient deionized water for 24 h, with the water changed twice during this period. Afterward, it was hung to dry for 25 h at 20°C, RH = 45%, and RH = 65%, respectively. The macroscopic morphology of the obtained CS / CA composite monofilament is shown below. Figure 6a and Figure 6b As shown. Figure 6a The macroscopic morphology of the composite monofilament was captured by a 12-megapixel camera; Figure 6b This image was taken using a 16-megapixel stereo microscope at 8x magnification.

[0088] The obtained monofilaments, under a dry state with RH = 65%, exhibited a holding stress of 65.59 ± 2.23 MPa, representing an increase of approximately 47% compared to the uncrosslinked monofilaments. The tensile strength at break was 7.35% ± 0.92%, the unbound stress was 70.63 ± 5.87 MPa, and the tensile strength at break was 16.25% ± 8.11%. Under a dry state with RH = 45%, the holding stress was 87.97 ± 3.63 MPa, the tensile strength at break was 5.79% ± 0.91%, the unbound stress was 88.07 ± 5.27 MPa, and the tensile strength at break was 10.69% ± 4.49%. The dry-state holding stress of the CA ion-crosslinked CS monofilaments under both humidity conditions met the national standard threshold for single strands. For further improvement, post-stretching treatment using mechanical stretching can be performed on the monofilaments.

[0089] The safety and degradation performance of the composite monofilaments were tested as follows:

[0090] In the heavy metal content test, the sample extract, lead standard stock solution (0.1 mg / mL), and lead standard solution (1 μg / mL) were reacted with thioacetamide reagent under weakly acidic conditions to compare the color development. The experimental results of the color development of heavy metal reactions are as follows: Figure 7 As shown: where the following is used Figure 6a The sample extract (C) was obtained by extracting CS / CA composite monofilament suture. The color of sample extract (C) was significantly lower than that of lead standard stock solution (A) and lead standard solution (B). Against a white paper background, the sample extract did not show any color development when reacting with thioacetamide solution under weakly acidic conditions, indicating that the heavy metal content in the monofilament suture was negligible and met the requirements for absorbable surgical sutures in the National Standard of the People's Republic of China—GB / T14233.1-2008.

[0091] In the in vitro enzymatic degradation experiment, the in vitro enzymatic degradation performance of monofilament suture samples was characterized by three methods: sample residue rate, SEM morphology analysis after enzymatic hydrolysis, and BSR (residual stress value). One hundred monofilament suture samples (each approximately 110 mm long after cutting) were randomly selected and divided into 5 groups. Before enzymatic hydrolysis, the total mass of each group of monofilament sutures was weighed and recorded as m0. Each group was immersed in 50 mL of 1 mg / mL lysozyme phosphate solution (pH = 7.4, c = 0.1 mol / L) and placed in an air bath constant temperature shaker, with the temperature set at 37℃. The 50 mL of fresh 1 mg / mL lysozyme phosphate solution was replaced every three days. Samples were removed at weeks 1, 2, 3, 4, and 5, and the monofilament sutures were washed with deionized water before testing.

[0092] Test results are as follows Figure 8 , Figure 9 , Figures 10a to 10e As shown, after 5 weeks of in vitro enzymatic degradation in a simulated human environment, the monofilament sutures still maintained a high residual rate and a BSR (body surface roughness) of approximately 80%. SEM images show that within 5 weeks of in vitro enzymatic degradation, the surface of the composite monofilament sutures was smooth, without excessively large bumps or pits. The curve showing the change in the residual rate of the monofilament sutures after in vitro enzymatic degradation over time is shown below. Figure 8 As shown, the horizontal axis represents time in weeks, and the vertical axis represents the residual rate (%). The change in BSR over time after in vitro enzymatic degradation of composite monofilament sutures is illustrated below. Figure 9 As shown, the horizontal axis represents time in weeks, and the vertical axis represents the stress value (BSR) in percentages.

[0093] Figures 10a to 10e Scanning electron microscope images of CS / CA composite monofilament sutures after 5 weeks of in vitro enzymatic degradation: Figure 10a (a) refers to the first week; Figure 10b (b) is the second week; Figure 10c (c) refers to the third week; Figure 10d (d) refers to the fourth week; Figure 10e (e) refers to the fifth week.

[0094] In the cytotoxicity test, the monofilament suture cytotoxicity test was performed according to the extract method specified in 10.3 of GB / T 16886.12-2017. Simultaneously, the results of the extract method were analyzed according to 8.5 of GB / T 16886.5-2017 to determine the cytotoxicity level. The specific operating procedure is as follows:

[0095] (1) Preparation of extract

[0096] The monofilament sutures were sterilized at 120°C using a vertical pressure steam sterilizer. After sterilization, the sutures were placed on a clean bench and air-dried under UV light for 24 hours. The monofilament sutures were then extracted in DMEM at an extraction ratio of 0.1 g / mL and allowed to stand at a constant temperature of 37°C for 24 hours. The mixture was then filtered, and the filtrate was collected for later use.

[0097] (2) MTT assay for cytotoxicity

[0098] The MTT assay detects cell viability based on the activity of succinate dehydrogenase in the mitochondria of living cells. When thiazolyl blue (MTT) is added to living cells, MTT is reduced by the enzyme to water-insoluble blue-purple crystals, a phenomenon not observed in dead cells. After dissolving the blue-purple crystals in DMSO, the absorbance is measured at 490 nm using an enzyme-linked immunosorbent assay (ELISA) reader. The cytotoxicity of the added substance is analyzed by comparing it with the control group.

[0099] L929 and Hacat cells were seeded into 96-well plates, with 6 × 10³ cells per well and a volume of 100 μL per well. The outermost wells were filled with the same volume of sterile phosphate buffer. Cells were incubated at 37°C with 5% CO2 for 24 hours until adherence. Six replicates were established, with surgical suture extract added to the experimental group and an equal volume of DMEM added to the control group. Incubation times were 1, 2, and 3 days. After incubation, cell morphology was observed using a fluorescence microscope to preliminarily assess cell viability. 25 μL of 5 mg / mL LTT sterile phosphate buffer was added to each well, and incubation continued for 2–4 hours. The culture medium was then removed, and 150 μL of DMSO was added to each well to dissolve the blue-purple crystals. After thorough mixing, the absorbance (OD value) of each well was measured at 490 nm using a microplate reader.

[0100] The formula for calculating cell viability is:

[0101]

[0102] According to C.2.5 in Appendix C of GB / T 16886.5-2017, when the survival rate is low, the experimental sample has high potential cytotoxicity. For example, if the survival rate drops to less than 70% of the control, it has potential cytotoxicity.

[0103] (3) Cytotoxicity rating

[0104] Cell toxicity (L929, Hacat) was qualitatively evaluated by examining cells under a microscope and observing changes in cell morphology, vacuolation, shedding, and cell lysis. The morphological classification of cytotoxicity of extracts is shown in Table 1.

[0105] Table 1

[0106]

[0107]

[0108] Figures 11a to 11f This is a graph showing the changes in cell number and morphology over three days after Hacat administration. Figures 11a to 11c For the CS / CA group, 1-3 days; Figure 11d (d) to Figure 11f (f) is the control group for days 1–3. Figures 11d to 11f Compared with the control group, the cell morphology of the control group was different on days 1-3. Figure 11a (a) to Figure 11c (c) In the CS / CA group, no significant changes in cell morphology were observed from day 1 to day 3, and no excessive cell death was observed, indicating that the extracts of the two monofilament sutures had no significant toxic effect on the cells. Large-volume "squamous" Hacat structures were also observed, indicating good cell viability. Furthermore, in terms of cell count, compared to the control group, the CS / CA group did not show a significantly lower cell count at the same number of days, nor did it show a significant decrease in cell count over time. Therefore, in the experiment, no more than 20% of the cells were rounded, loosely adherent, without intracytoplasmic granules, or showing any morphological changes; there was virtually no cell lysis, and no cell growth inhibition was observed, indicating that the cytotoxicity of this sample was ≤1.

[0109] Hacat's survival rate changes over time as follows: Figure 12As shown, the horizontal axis represents time in hours (h), and the vertical axis represents cell survival rate in percentage (%). Data analysis shows that the survival rate of Hacat cells in the CS / CA group varied with the number of days (1d, 2d, and 3d) at 107.95±8.70%, 109.27±2.30%, and 104.18±11.10%, respectively, maintaining a high level (>100%), indicating a certain cell growth-promoting effect. Therefore, when CS / CA composite monofilament surgical sutures are applied to humans, they do not exhibit potential skin cell and tissue toxicity, showing the potential to promote epidermal cell growth and thus benefit wound healing.

[0110] Changes in cell number and morphology within three days of L929 drug administration are as follows: Figures 13a to 13f As shown, Figure 13a (a) to Figure 13c (c) For the CS / CA group, 1–3 days; Figure 13d (d) to Figure 13f (f) is the control group for days 1–3. On day 1, compared with... Figure 13d Compared to the diagram, Figure 13a The number of cells did not decrease significantly, nor did more than 20% of the total cells die. The cells maintained good morphology, appearing flat and slender. Starting from the second day, compared to the control group, the number of cells in the CS / CA group increased, and the cell density was higher than that in the control group. The cells in the experimental group maintained good morphology, and no more than 20% of the total cells died. By the third day, the number of cells in the control group had increased significantly compared to the second day, indicating that the L929 cells had good viability, but compared to the control group... Figures 13a to 13c The number of cells in the CS / CA group has overwhelmingly exceeded Figures 13d to 13f The control group in the study indicated that the CS / CA composite monofilament suture promoted the proliferation of L929 cells to some extent. Throughout the process, no more than 20% of the cells in the CS / CA group showed rounded, loosely adherent, and morphologically altered appearance without intracytoplasmic granules; there was virtually no cell lysis, and the suture significantly promoted cell growth, indicating that the cytotoxicity of this sample was ≤1.

[0111] The survival rate of L929 over time is as follows: Figure 14As shown, the horizontal axis represents time in hours (h), and the vertical axis represents cell survival rate in percentage (%). Data analysis showed that the survival rate of L929 cells in the CS / CA group varied with the number of days (1d, 2d, 3d) as follows: 109.64±10.28%, 108.01±14.33%, and 113.14±14.33%, respectively. Throughout the experiment, the survival rate of L929 cells remained at a high level (>100%), indicating a certain cell growth-promoting effect, with the survival rate showing a fluctuating upward trend. According to GB / T 16686.5-2017, when the survival rate is greater than 70% of the control group, it indicates that the sample does not have potential cytotoxicity. Therefore, when the CS / CA composite monofilament surgical suture is applied to humans, it not only does not have potential skin cell and tissue toxicity but also has the potential to promote cell growth, making it a potential excellent absorbable surgical suture.

[0112] The above description, in conjunction with specific preferred embodiments, provides a further detailed explanation of the present invention. It should not be construed that the specific implementation of the present invention is limited to these descriptions. For those skilled in the art, several equivalent substitutions or obvious modifications can be made without departing from the concept of the present invention, and all such modifications, achieving the same performance or purpose, should be considered within the scope of protection of the present invention.

Claims

1. A method for preparing an absorbable monofilament suture, characterized in that, Includes the following steps: S1. Dissolve chitosan in a dilute acid solution to form a spinning solution; S2. The spinning solution is sequentially filtered and vacuum degassed. S3. The spinning solution treated in step S2 is extruded through a spinneret into a coagulation bath to form nascent fibers. S4. The nascent fibers are washed with water. S5. The nascent fibers treated in step S4 are immersed in a polycarboxylic acid solution to carry out an ionic crosslinking reaction. S6. The fibers after the ion crosslinking reaction in step S5 are sequentially washed and dried to obtain absorbable monofilament sutures.

2. The method as described in claim 1, characterized in that, In step S1, the chitosan has a degree of deacetylation greater than 84.5% and a molecular weight greater than 7.0 × 10⁻⁶. 6 The volume percentage concentration of the dilute acid solution is 1.0% to 3.0%; the mass-volume percentage concentration of the solids in the spinning solution is 1% to 4%.

3. The method as described in claim 1, characterized in that, In step S2, the filtration process uses a 250-400 mesh filter cloth for vacuum filtration; the vacuum degassing process takes 1-5 hours.

4. The method as described in claim 1, characterized in that, In step S3, the coagulation bath contains ethanol with a mass percentage concentration of 1.0 to 4.5% and sodium hydroxide with a mass percentage concentration of 2.0 to 6.0%.

5. The method as described in claim 1, characterized in that, In step S3, after the spinning solution is extruded from the spinneret, a constant exhaust pressure of 0.5 to 0.9 MPa is applied to the spinneret.

6. The method as described in claim 1, characterized in that, In steps S4 and S6, the water washing process includes soaking in sufficient deionized water for 12 to 36 hours, changing the water 1 to 3 times during this period.

7. The method as described in claim 1, characterized in that, The drying process in step S6 includes hanging the product to air dry for 26 to 36 hours at a temperature of 15 to 25°C and a relative humidity of 45 to 75%.

8. The method as described in claim 1, characterized in that, In step S5, the mass percentage concentration of the polycarboxylic acid solution is 10-30%, and the polycarboxylic acid is one of citric acid, tartaric acid, malic acid, or succinic acid.

9. The method as described in claim 1, characterized in that, In step S5, the pH of the polycarboxylic acid solution is adjusted to 5.5–6.5 using sodium hydroxide solution, the reaction temperature is 20–90°C, and the reaction time is 1–3 hours.

10. An absorbable monofilament suture, characterized in that, Prepared by the method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Method of and apparatus for fluid filtration and the like with the aid of chitosan

    US4018678A